Investigation of the Pore Structure and Morphology of Cellulose Acetate Membranes Using Small-Angle Neutron Scattering. 1. Cellulose Acetate Active Layer Membranes - Kulkarni, Sandeep; Krause, Sonja; Wignall, G. D; Hammouda, B (Macromolecules, 1994)
The structure of ultrathin cellulose acetate membranes, known as active layer membranes, has been investigated using small-angle neutron scattering. These membranes are known to have structural and functional similarity to the surface or 'skin' layer in commercial reverse-osmosis (RO) membranes and hence are useful model systems for understanding the structure of the RO membrane skin layer. Active layer membranes were studied after swelling them with either D sub(2)O or CD sub(3)OD. The results in both cases clearly indicated the presence of very small (10-20 angstrom) porous structures in the membrane. The presence of such pores has been a subject of long-standing controversy in this area. The data was analyzed using a modified Debye-Bueche analysis and the resultant membrane structure was seen to agree well with structural information from electron microscopic studies. Finally, a possible explanation for the differences in scattering observed between the D sub(2)O swollen membranes and the CD sub(3)OD swollen membranes has been presented.